Determination Of Total Flavonoid Content Of Yellow Wood (Arcangelisia Flava (L.) Merr) Extract And Antibacterial Activity Against Staphylococcus aureus - Maryanti Yuza; Ridwanto Ridwanto; Zulmai Rani (Journal of Agromedicine and Medical Sciences, 2023)
Yellow wood (Arcangelisia flava) is a medicinal plant that has received little attention. Merr and (L.). Yellow wood has antibacterial, antioxidant, anti-hyperlipidemic, and anti-cancer properties. Furthermore, yellow wood is known to contain a range of flavonoid compounds, such as hydroxylarcangelicin, which has broad antibacterial activity. The purpose of this research is to investigate the total flavonoid content of yellowwood extract as well as its antibacterial activity against Staphylococcus aureus bacteria. The manufacturing of methanol extract, characterization of simplisia, phytochemical screening, and determination of the total flavonoid levels of the yellow wood methanol extract by a visible spectroscopic approach were all part of this stage of research. Next, use chloramphenicol as a positive control and dimethyl sulfoxide (DMSO) as a negative control to test antibacterial activity against Staphylococcus aureus. The results of this study can be concluded to show that the total flavonoid levels in the methanol extract of yellow wood at a metanol concentration of 80% were 228,314 ± 5,4171 mg QE/g. At a 90% concentration of 245.993 ± 6.7626 mg QE/g and a 100% concentration of 265.953 3.0853 mg QE/g. Keywords: Yellow wood; Flavonoids; Spektrofotometri Visible; Stphylococcus aureus;